Pengalaman Pasien Pertama Kali Terdiagnosis HIV/AIDS: Studi Fenomenologi Dalam Perspektif Keperawatan - Welly Vitriawan; Ratna Sitorus; Yati Afiyanti (Jurnal Keperawatan Indonesia, 2007)
AbstrakSuatu studi fenomenologi telah dilakukan untuk mengeksplorasi berbagai pengalaman pasien pertama kali terdiagnosis HIV/AIDS termasuk pengalaman menerima pelayanan kesehatan dari para praktisi kesehatan. Data studi ini diperoleh dari 6 partisipan, dikumpulkan melalui wawancara formal tidak berstruktur yang mendalam sebanyak dua kali di ruang rawat khusus HIV/AIDS RS X di Jakarta. Wawancara direkam kemudian dibuat dalam bentuk transkrip wawancara. Hasil penelitian mengungkapkan variasi berbagai pengalaman pasien pertama kali terdiagnosis HIV/AIDS. Setiap pasien dalam studi ini saat pertama kali terdiagnosis HIV/AIDS mengalami stress. Pasien juga mengalami proses berduka. Berbagai mekanisme koping dan adaptasi telah dilakukan pasien. Selain itu setiap pasien pertama kali terdiagnosis HIV/AIDS membutuhkan dukungan dari lingkungan sekitarnya terutama dari keluarga, pasangan, teman terdekat, dan petugas kesehatan. Pasien juga membutuhkan pelayanan keperawatan termasuk membutuhan perawat yang bersikap baik dan komunikatif. Hasil studi ini diharapkan perawat medikal bedah akan lebih memahami harapan pasien HIV/AIDS untuk dapat meningkatkan kualitas hidup. AbstractThis a phenomenology study which aims to understand the diverse of patients’ first time experiences when they were diagnosed with HIV/AIDS included experience accepted of health care. The data collection from six participants with deep interviewed in the X Hospital in Jakarta. Interview recorded thus transcripted. The findings showed that the patients’ first time experiences when diagnosed with HIV/AIDS were depicted emotionally and filled with thematic expressions. It was concluded from this study that the physical, psychological and social stress were considered as the first time experiences of patients when diagnosed with HIV/AIDS. Whilst the first grieving process experienced by the patients. The coping mechanisms identified as the first time experiences were the openness to others, self motivated, and struggled to adapt to the any circumstances. The research findings suggested that the first time experiences of every patient when diagnosed with HIV/AIDS required supports primarily from relatives, spouse, significant friends and health care providers. The needs to the nursing care and good behaviors and communication of nurses were also included as the first needs and expectations of the patients to the nurses. Furthermore, the study also made suggestions that supports, recognition and improvement of the nursing service provided for the first time experience of patients being diagnosed with HIV/AIDS, in turn, would lead to the better patients’ live and reassure the quality of nursing care